Menggali Potensi Kewirausahaan di Era Digital: Tantangan dan Peluang - Sofia Zahra; Zyhan Risty Andini; Leoni Sabrilina Putri; Mansur Keling (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
Modern technology is developing very rapidly. The impact of artificial intelligence on economic activity. This also happens in web-based applications. Rapid progress makes company competition increasingly tighter and more intense. The aim of this research is to see how entrepreneurship has increased in the current digital era and what opportunities and challenges are faced. The method in this research is library research using book literature, journals and other electronic records. Technology in this digital era is developing very rapidly, but there are challenges and opportunities in this digital era, namely the high level of competition among business opportunities entrepreneurs. The younger generation now has more opportunities to develop their entrepreneurial skills thanks to digital technology.